Molecular dynamics simulations of theoretical cellulose nanotube models. (15th June 2018) - Uto, Takuya; Kodama, Yuta; Miyata, Tatsuhiko; Yui, Toshifumi
Graphical abstract: Highlights: The cellulose nanotube; a novel superstructure of cellulose, were predicted by theoretical calculations. The one-quarter chain staggering relationship between adjacent chains were proposed as a general architecture of the cellulose nanotube. Frequent rotations of the hydroxymethyl groups were coupled with exchanges in the hydrogen bonds on the tubular cellulose walls. A hydrophobic nature of the cellulose nanotube surfaces was suggested by solvent structuring. Abstract: Nanotubes are remarkable nanoscale architectures for a wide range of potential applications. In the present paper, we report a molecular dynamics (MD) study of the theoretical cellulose nanotube (CelNT) models to evaluate their dynamic behavior in solution (either chloroform or benzene). Based on the one-quarter chain staggering relationship, we constructed six CelNT models by combining the two chain polarities (parallel ( P ) and antiparallel ( AP )) and three symmetry operations (helical right (HR ), helical left (HL ), and rotation (R)) to generate a circular arrangement of molecular chains. Among the four models that retained the tubular form ( P -HR, P -HL, P -R, and AP -R), the P -R and AP -R models have the lowest steric energies in benzene and chloroform, respectively. The structural features of the CelNT models were characterized in terms of the hydroxymethyl group conformation and intermolecular hydrogen bonds. Solvent structuring more clearly occurred with benzene than chloroform, suggesting that the CelNT models may disperse in benzene.